Perancangan Ui/Ux Aplikasi E-Commerce Berbasis Website Pada Toko Aema Kacamata Surabaya Menggunakan Model Lean User Experience - Anis Dwi Setyani; Ayouvi Poerna Wardhanie; Sulistiowati - (Jurnal Sistem Informasi Universitas Dinamika, 2021)
The AEMA Glasses store is a shop that sells various accessories that was founded in 2010, the shop provides various driving accessories such as glasses, cloth slayer, mask buff, gloves, hats, masks and belts. Currently the AEMA Glasses shop is only a shop, so the buying and selling process only occurs in that shop. This is a drawback for this store because customers who want to order from outside the area cannot be served quickly and customers also cannot see the catalog available in the store. In addition, shop employees also experience difficulties in recording sales and calculating shop turnover because this AEMA shop still uses books and a calculator in the transaction process, which causes frequent differences in the number of goods calculations.Based on the existing problems, a web-based UI / UX design solution was found with the Lean UX method which consists of several stages, including Declare Assumption, Create MVP, Run an Experiment, and Feedback and Research. By including 30 samples, namely AEMA Glasses shop customers and 7 samples, namely AEMA Glasses store employees, so a total of 37 samples.Based on the results of the analysis and observations that have been made, a prototype design was made using the Lean UX method which was then tested on AEMA Glasses customers and AEMA Glasses employees which resulted in the success rate of prototype testing for customers reaching 72% and the success rate of prototype testing for admins reaching 86%.